Metallic porous iron nitride and tantalum nitride single crystals with enhanced electrocatalysis performance - Zhang, Feiyan (2021)
Altering a material's catalytic properties would require identifying structural features that deliver electrochemically active surfaces. Single-crystalline porous materials, combining the advantages of long-range ordering of bulk crystals and large surface areas of porous materials, would create sufficient active surfaces by stabilizing 2D active moieties confined in lattice and may provide an alternative way to create high-energy surfaces for electrocatalysis that are kinetically trapped. Here, a radical concept of building active metal–nitrogen moieties with unsaturated nitrogen coordination on a porous surface by directly growing metallic porous metal nitride (Fe3N and Ta5N6) single crystals at unprecedented 2 cm scale is reported. These porous single crystals demonstrate exceptionally high conductivity of 0.1–1.0 × 105 S cm−1, while the atomic surface layers of the porous crystals are confirmed to be an Fe termination layer for Fe3N and a Ta termination layer for Ta5N6. The unsaturated metal–nitrogen moieties (Fe6–N and Ta5–N3) with unique electronic structures demonstrate enhanced electrocatalysis performance and durability.